2011
DOI: 10.1109/tnano.2010.2041010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrostatic Integrity for Ultrathin-Body Germanium-On-Nothing MOSFET

Abstract: This paper examines the electrostatic integrity of ultrathin-body (UTB) germanium-on-nothing (GeON) MOSFET using theoretically calculated subthreshold swing from the analytical solution of Poisson's equation. Our results indicate that UTB GeON MOSFETs with the ratio of channel length (L g ) to channel thickness (T ch ) around 4 can show comparable subthreshold swing to that of the silicon-on-nothing counterparts. The impact of buried insulator (BI) thickness (T B I ) and BI permittivity on the electrostatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…(18) of the threshold-voltage model. The simulated results exhibit good agreement with TCAD data [16], showing the applicability of the SS formula for Ge UTB MOSFET, thus indirectly supporting the validity of the threshold-voltage model. It is observed that SS decreases as the channel thickness is reduced, indicating that thin channel can improve the sub-threshold performance of the device.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…(18) of the threshold-voltage model. The simulated results exhibit good agreement with TCAD data [16], showing the applicability of the SS formula for Ge UTB MOSFET, thus indirectly supporting the validity of the threshold-voltage model. It is observed that SS decreases as the channel thickness is reduced, indicating that thin channel can improve the sub-threshold performance of the device.…”
Section: Resultssupporting
confidence: 63%
“…The validity of the model is confirmed by comparing with experiment data [15] and the full-depleted SOI (FDSOI) MOSFET model [15]. To further confirm the validity of the model, subthreshold swing is also derived based on the surface potential and the simulated results for GeON MOSFET exhibit good consistence with the results of technology computer-aided design (TCAD) simulation [16]. The influences of some structural and physical parameters on the threshold behavior are discussed.…”
Section: Introductionmentioning
confidence: 67%
“…For long-channel UTB MOSFETs, the conduction band edge E C (x) was usually treated as a triangular well in the past [4]. However, to account for the source/drain coupling for short-channel devices, the conduction band edge E C (x) in (1) should be treated as a parabolic well [5] E C (x) = αx 2 + βx + γ where α, β, and γ are channel-length-dependent coefficients and can be obtained from the channel potential solution of Poisson's equation under subthreshold region [6]. Under the parabolic-well treatment, the solution of (1) can be expressed as Ψ j (x) = ∑ d n • x n with the coefficients d n 's [3]:…”
Section: Analytical Solution Of Schrödinger Equationmentioning
confidence: 99%
“…Almost all results have focused on the fabrication process associated with a Ge JL transistor [39][40][41][42][43][44][45][46][47][48][49][50][51]. Only a few studies on subthreshold operation of conventional inversion mode transistors with Ge as the channel material are available in the literature [52][53][54][55][56][57]. These models, developed for inversion mode transistors, cannot be directly applied for Ge JL devices with wider underlap regions.…”
Section: Introductionmentioning
confidence: 99%